2019
DOI: 10.1073/pnas.1821761116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microstructure formation on the stability of vapor-deposited glasses

Abstract: Glasses formed by physical vapor deposition (PVD) are an interesting new class of materials, exhibiting properties thought to be equivalent to those of glasses aged for thousands of years. Exerting control over the structure and properties of PVD glasses formed with different types of glass-forming molecules is now an emerging challenge. In this work, we study coarse grained models of organic glass formers containing fluorocarbon tails of increasing length, corresponding to an increased tendency to form micros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…By measuring the relaxation dynamics of thin glassy TNB and α,α-A films, Samanta et al concluded that while the bulk of the glass is in a deeply quenched glassy state, the molecules within 10 nm from the surface can have a faster dynamics and are able to equilibrate before becoming part of the bulk [122]. Similar conclusions are obtained by More et al [145]. They used molecular dynamics simulations to study empirical coarsegrained models of organic molecules containing model fluorocarbon tails of increasing length: zero, one, four, and eight fluorocarbons, with a structure composed of a phenyl "body" and a fluorocarbon "tail", to simulate the formation of a vapor deposited glass.…”
Section: Surface Relaxationmentioning
confidence: 55%
“…By measuring the relaxation dynamics of thin glassy TNB and α,α-A films, Samanta et al concluded that while the bulk of the glass is in a deeply quenched glassy state, the molecules within 10 nm from the surface can have a faster dynamics and are able to equilibrate before becoming part of the bulk [122]. Similar conclusions are obtained by More et al [145]. They used molecular dynamics simulations to study empirical coarsegrained models of organic molecules containing model fluorocarbon tails of increasing length: zero, one, four, and eight fluorocarbons, with a structure composed of a phenyl "body" and a fluorocarbon "tail", to simulate the formation of a vapor deposited glass.…”
Section: Surface Relaxationmentioning
confidence: 55%
“…However, after the oligomers have combined to make larger chains (equilibrium chain length ∼200 atoms per chain) within 10 −6 to 10 −4 s (33), the barrier for relaxation is increased. The interaction between the oligomers can potentially slow the surface mobility and reduce the depth of the mobile region, limiting the packing efficiency during SME, analogous to what has been observed in molecular SGs with strong intermolecular interactions (5,16,35).…”
Section: Resultsmentioning
confidence: 79%
“…It is understood that SG formation is due to enhanced surface mobility (5,8,12,(14)(15)(16)(17). When T dep < Tg , at slow deposition rates (∼0.2 nm/s for most organic glasses), the surface region has sufficient mobility (18) to reach more energetically favored states before being buried into dynamically arrested states.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The amphiphilic nature of posaconazole may be responsible for its vertical orientation at the free surface of the liquid. In recent simulations of vapor-deposited glasses of amphiphilic fluorinated molecules, the fluorinated tails segregate to the surface (49); it is plausible that posaconazole behaves similarly during deposition, and this provides a guide in selecting additional systems for study. Our investigation of posaconazole was motivated by its structural similarity with itraconazole, a system known to form smectic liquid crystals.…”
Section: Discussionmentioning
confidence: 99%